Abusive pricing practices by online platforms: a framework review of Article 102 TFEU for future cases. (6th February 2022) - Mandrescu, Daniel
Abstract: The challenges involved in the application of Article 102 TFEU to online platforms have become the main topic of debate in the context of EU competition policy in digital markets. This debate has recently also extended to the topic of platform pricing with the complaints about the pricing strategies of Apple with respect to its App Store and it is a matter of time before similar complaints will follow with respect to other prominent platforms. Applying the current framework of price related abuses under Article 102 TFEU to the pricing practices of online platforms will, however, require adapting the respective legal tests of abuse to the commercial reality of these actors. Doing so will inevitably entail accounting for their multisided nature which would sometimes require that the assessments of abuse extend to more than one side of the platform. Furthermore, such legal assessments would also have to consider the special role played by platform pricing as a coordination tool for getting multiple types of customer groups on board with the aim of facilitating profitable interactions between them. Therefore, this article seeks to explore how the current frameworks for price-related abuses could be applied and, if needed, adapted so as to fit the commercial reality of online platforms. The aim of this effort is to provide guidance for ongoing and future cases so as to prevent legitimate pricing practices from being erroneously scrutinized as well as to prevent anti-competitive pricing practices from escaping legal scrutiny due to the intricacies of platform pricing schemes.